Martin Luther: Prophet to The Church Catholic - Atkinson, James (Scottish journal of theology, 1984)
Controversy forced Luther into a confessional position which history has hardened almost into a kind of denominationalism. The subsequent rise of the ‘Lutheran’ Church, and of ‘Lutheran’ theology, owing to Luther's excommunication and his exclusion from the Roman Catholic Church, have contributed to a general acceptance of this evaluation. Save for a few distinguished Roman Catholic and Protestant scholars, who have worked on the sources and allow Luther to speak for himself, most historians, and certainly the general reader, work on the assumption that Luther is such a ‘confessional’ figure. To find a truer understanding of Luther, of what he was concerned to say to the Church of his day, it is necessary to detach him from this confessional, denominational location by setting him in the Catholic environment in which he was born, in which he was educated, and to which he felt called by God to speak the Word of God. He should be seen as a reformer of a Catholicism which had largely become de-spiritualised and secularised. He offered a reformatio of that which had suffered a de-formatio, and did so for the sake of God, propter deum, as he put it. He sought only to reform a Catholicism which he loved, and to reform it, not as he thought fit, but according to the intent of Jesus Christ and his Apostles, and that on the lines of solid biblical scholarship, authentic tradition and fair argument.